Pemberdayaan Ibu dalam Pemanfaatan Pangan Lokal Berbasis Ikan Campur untuk Mencegah Stunting: Sebuah Studi Refleksi dalam Penelitian Aksi Partisipatif: Empowering Mothers in Utilizing Local Food Based on Mixed Fish to Prevent Stunting: A Reflection Study in Participatory Action Research - Pasaribu, Rina Doriana; Nasution, Erlina; Angkat, Abdul Chairudin (Amerta Nutrition, 2025)
Background: Stunting remains a significant public health issue, particularly in low-resource settings where maternal knowledge and dietary practices influence child nutrition. Empowering mothers through participatory approaches is an effective strategy for addressing this challenge. Objectives: This study examined the reflective process within the Participatory Action Research (PAR) framework to empower mothers to enhance their child nutrition through local food resources. It specifically focuses on the critical reflections that shape the effectiveness of empowerment. Methods: This study employed PAR with a focus on the reflection stage, to assess the effectiveness of maternal empowerment in utilizing local food for stunting prevention. Quantitative assessments including structured questionnaires were administered to 50 randomly selected participants. A paired t-test was conducted to analyze changes in knowledge and attitudes, with statistical significance set at p-value<0.05. Results: The reflection phase revealed a significant increase in maternal knowledge and attitude post-intervention. The mean knowledge score improved from 14.70±3.09 to 29.60±0.97 (p-value=0.001), while the attitude score increased from 11.50±3.06 to 19.30±1.52 (p-value=0.001). The maternal empowerment program was well received, with trained health cadres and PKK (family welfare movement) mothers playing a crucial role in fostering sustainable behavioral change in stunting prevention. Conclusions: Critical reflection on PAR enhances the effectiveness of maternal empowerment. These findings offer practical insights for policymakers and public health practitioners in designing adaptive community-driven nutritional interventions. Integrating reflective practices ensures that stunting prevention programmes are contextually relevant, sustainable, and scalable across diverse sociocultural settings.